A Work study on Pilipinas Kao Incorporated - Tan, Kerwin; Tan, Alfred; Uy, Edward (Diliman, Quezon City College of Engineering, 1992)
The study is about the system of filling and packaging shampoo bottles at Pilipinas Kao, Inc. The system is composed of three operations namely : the forming of carbon boxes, filling of boxes with shampoo, and the checking of the packaged/sealed boxes ready for delivery. The group has aimed to increase system productivity or the quantity of outputs. Last year's productivity was disclosed by management at 55 percent of the standard. However, further details were withheld. After conducting a thorough investigation of the present system, several flaws were detected. The foremost of which is the excessive waiting time and the unnecessary rests associated with the checking operation. Furthermore, inefficient methods and improper placement of raw materials were being tolerated in the box-forming operation. Aside from this, the box-former experienced discomfort while sitting on his chair without an backrest. Changes in the method and procedure employed and the utilization of simple but effective tools were made to increase the efficiency as well as the productivity of the system. After conducting the cost and benefits, the group was able to give general several proposals which greatly increased worker productivity and improved working conditions. A new layout and an improved two-handed activity chart were proposed for both operations. Based on, computations, an additional 190 packaged boxes can be produced from the proposed methods. This study was primarily aimed towards the improvement of the system of filling and packaging shampoo bottles to live up to Pilipinas Kao's committment to provide a regular supply of quality products to the market.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Pilipinas Kao Incorporated; Coconut products; Systems analysis